Impact of hemoglobin levels on acute ischemic stroke severity - Abuhulayqah, Shaima; Aldulijan, Fajar Abdulrazzak; Turkistani, Alaa Nabil; Almulhim, Albatoul Fahad; Almulhim, Cereen Fahad; Bashir, Shahid; Ali, Eman Nassim (Frontiers in Neurology, 2025)
IntroductionStroke is one of the most common causes of disability and mortality worldwide. In Saudi Arabia, it is a crucial health issue. Ischemic stroke is the most common type of stroke in this area, and understanding its relationship with hemoglobin (Hgb) levels is vital. To date, no study has established an exact relationship between Hgb levels and stroke severity. This study assessed the association between Hgb levels and the severity of acute ischemic stroke (AIS) at presentation.MethodsWe conducted a retrospective study of patients admitted and diagnosed with AIS between 2013 and 2017. The exclusion criteria included other stroke types (such as hemorrhagic or venous infarction), patients with a history of internal bleeding, and pregnant and lactating women. The patients were divided into three groups based on Hgb levels: low, average, and high. Correlations were analyzed between these groups and the National Institutes of Health Stroke Scale (NIHSS) scores, stroke outcomes at discharge (cured, improved, or mortality decreased), and stroke subtype, as determined and classified by the TOAST classification criteria.ResultsThe Pearson correlation coefficient showed a weak positive correlation between Hgb levels and NIHSS scores. Neither stroke outcomes nor stroke types showed significant correlations with mean Hgb level.ConclusionThe results of this retrospective study on a small cohort of patients diagnosed with AIS indicate that higher Hgb levels at hospital admission are associated with greater stroke severity, as measured by the NIHSS score. However, no significant effect was observed on stroke outcome at discharge or the TOAST classification.